Development of a piezoelectric based DC to DC converter for micro energy harvesting system - Mostafa, Mohammad Golam
Nowadays renewable energy and its harvesting are attractive, because this energy is free which leads to reduce energy cost. One of the common energy harvesting (EH) technique is a piezoelectric based system. But the piezoelectric based technique needs to be improving as this system is highly capacitive rather than resistive which limits the current of a resistive load. The efficient way to harvest the energy from the system mostly depends on its interfacing circuitry. It is necessary to characterize and optimize the interfacing circuit for maximizing the output power. Piezoelectric transducer (PZT) has a capacitive in nature as a result of low frequency, the harvesting system needs a larger value of inductor for cancelling the capacitive effect. This phenomenon makes the interface circuit bulky. An efficient interfacing circuit has been designed that reduces the inductance by adding a capacitor in parallel with the inherent capacitance of the PZT to increase the overall capacitance in the circuit. The parameters of the circuit which are duty cycle, switching frequency, inductance and load resistance have been characterized and optimized to improve the efficiency of the harvesting system. The developed design is able to work simultaneously as series and parallel resonant converter which reduces the overall inductor value of the circuit. In addition, it improves the impedance isolation between input and output and it also works as a single polarity power supply. By using frequency 13 kHz, duty cycle, 10%, inductance,13.2 µH for 60Ω output load, the maximum power, 280 mW have been obtained. Pspice 16.5 software has been used for simulation purposes. Simulated result has been compared with the closely related work and resulting in power performance efficiency of 47% more has been achieved. The application of harvested energy can be used in embedded sensor in buildings, medical and remote wireless sensor, RFID, biomedical implants, laptops, notepad and so on.